2007
DOI: 10.1016/j.jmb.2007.02.078
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Thermophilic Protein Complex Stabilized by Topologically Interlinked Chains

Abstract: A growing number of organisms have been discovered inhabiting extreme environments, including temperatures in excess of 100 °C. How cellular proteins from such organisms retain their native folds under extreme conditions is still not fully understood. Recent computational and structural studies have identified disulfide bonding as an important mechanism for stabilizing intracellular proteins in certain thermophilic microbes. Here, we present the first proteomic analysis of intracellular disulfide bonding in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 50 publications
4
90
0
2
Order By: Relevance
“…Catenanes are extremely rare in biology. We are aware of only 3 reports: the gp5 capsid protein of bacteriophage HK97 (63), the bovine mitochondrial peroxiredoxin III (64), and a Pyrobaculum aerophilum citrate synthase in which the catenanes are formed by disulfide bridging between the N-and C-terminal ends of each of the homodimer chains (65). The molecular mechanism of the catenane assembly in the Acidianus A1-3 enzyme is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Catenanes are extremely rare in biology. We are aware of only 3 reports: the gp5 capsid protein of bacteriophage HK97 (63), the bovine mitochondrial peroxiredoxin III (64), and a Pyrobaculum aerophilum citrate synthase in which the catenanes are formed by disulfide bridging between the N-and C-terminal ends of each of the homodimer chains (65). The molecular mechanism of the catenane assembly in the Acidianus A1-3 enzyme is not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies showed structural and biochemical evidence of the thermostabilizing effects of disulfide bonds on several proteins (3,4) and produced genomic and proteomic data that indicated prevailing disulfide bond formation in the cells of such thermophiles. For example, by using two-dimensional diagonal SDS-PAGE, they identified several intermolecular disulfide-bonded proteins from P. aerophilum (5).…”
Section: Importancementioning
confidence: 99%
“…Many thermostable proteins also have charged residues at their surfaces which can be involved in inter subunit interactions or increase the proteins solubility (Martin et al 2001). An increased number of disulfide bonds and Pro residues relative to mesostable enzymes both increase thermostability by constraining the conformation of the protein and making its unfolded form less favorable (Boutz et al 2007;Vieille and Zeikus 2001 and references there in). Conversely, Gly residues have the most degrees of conformational freedom of any amino acid in the polypeptide back-bone and are expected to encourage flexibility more than other residues.…”
Section: The Basis Of Protein Thermostability In Thermophilic Organismsmentioning
confidence: 99%